Ice-proximal sea ice reconstruction in the Powell Basin, Antarctica, since the Last Interglacial - W. W. Khoo; J. Müller; J. Müller; J. Müller; O. Esper; W. Xiao; C. Stepanek; P. Gierz; G. Lohmann; G. Lohmann; G. Lohmann; W. Geibert; et al. (Climate of the Past)
In Antarctica, the presence of sea ice not only plays a critical role in the climate system but also contributes to enhancing the stability of the floating ice shelves. Hence, investigating past ice-proximal sea ice conditions, especially across glacial–interglacial cycles, can provide crucial information pertaining to sea ice variability and deepen our understanding of ocean–ice–atmosphere dynamics and feedback. In this study, we apply a multiproxy approach, in combination with numerical climate modeling, to explore glacial–interglacial environmental variability. We analyze the novel sea ice biomarker IPSO25 (a di-unsaturated highly branched isoprenoid (HBI)), open-water biomarkers (tri-unsaturated HBIs; z-/e-trienes), and the diatom assemblage and primary productivity indicators in a marine sediment core retrieved from the Powell Basin, NW Weddell Sea. These biomarkers have been established as reliable proxies for reconstructing near-coastal sea ice conditions in the Southern Ocean (SO), where the typical use of sea-ice-related diatoms can be impacted by silica dissolution. We present the first continuous sea ice records, in close proximity to the Antarctic continental margin, since the penultimate deglaciation. Our data shed new light on the (seasonal) variability in sea ice in the basin and reveal a highly dynamic glacial–interglacial sea ice setting characterized by significant shifts from perennial ice cover to seasonal sea ice cover and an open marine environment over the last 145 kyr. Our results also unveil a stronger deglacial amplitude and warming during the Last Interglacial (LIG; Marine Isotope Stage (MIS) 5e) compared to the current one (Holocene). A short-term sea ice readvance also occurred towards the end of each deglaciation. Finally, despite similar findings between the proxy and model data, notable differences persist between both interglacials – emphasizing the necessity for different Antarctic ice sheet configurations to be employed and more robust paleoclimate data to enhance climate model performance close to the Antarctic continental margin.